James McHenry, Forgotten Federalist - KAREN E. ROBBINS (University of Georgia Press, 2013)
James McHenry’s life unfolds in stories. Writ large, the tale is of a man who tried to live his life honorably and make a diff erence. But this bigger narrative emerges from smaller ones that reveal important American—and human—themes. Initially, McHenry was a young immigrant looking for opportunity. He was ambitious for a new and better life, and in this sense he was a man on the make. But McHenry was aft er more than just a comfortable living; he wanted to rise in status, to become a gentleman, and to live by the gentleman’s code of honor. It certainly helped that his family arrived from northern Ireland with some property, enough to begin a dry goods importing business in the growing town of Baltimore. But that was only the beginning. McHenry also participated in his generation’s defi ning event—the American Revolution. McHenry climbed from the lowest rank of surgeon’s mate to serve on General George Washington’s staff , making contacts that opened doors for a future in politics, fi rst at the state and then at the national level. Equally important, James got to prove his manhood as citizen- soldier, off ering his life in service and possible sacrifi ce to the republic. His younger brother John was not so fortunate, as someone needed to stay in Baltimore to take care of their aging father and the mercantile business. John’s unhappiness over being left out of the Revolution led him to excessive behavior that ultimately killed him. The Revolution, of course, was an outgrowth of the Enlightenment, from which comes another theme. Enlightenment ideals led James McHenry to embrace fairly advanced views regarding the equality of men and women, as well as of the races, even if he was unable to live up to them fully. Benjamin Banneker, African American mathematician, requested and received from McHenry a laudatory introduction to Banneker’s almanac. Despite this, McHenry compromised for his convenience and chose to own domestic slaves. The slaves’ attempts to negotiate for their freedom become an important part of this story. In addition, although a youthful McHenry insisted upon the intellectual equality of men and women, the middle- aged McHenry thought his young daughter ought to be educated religiously, in order to learn to submit to her future husband. Two equal partners in a household, he thought, would only lead to confl ict.